Analyzing the Estimation of Energy Consumption in the Trajectory Planning of an Industrial Robot - Hosseini, Sara; Hahn, Ingo (2024 IEEE 19th Conference on Industrial Electronics and Applications, ICIEA 2024, 2024)
This paper introduces a method for estimating the energy consumption during trajectory planning tasks for an industrial robot (IR) arm manipulator. The study focuses on modeling the electrical and mechanical losses of a 6-Degree of Freedom (DoF) robot arm manipulator from Universal Robots. Correspondingly, a power losses cost function (PLCF) is proposed to calculate the electromechanical energy losses. The objective is to estimate energy losses during trajectory planning in Cartesian space for a tool center point (TCP), starting from an initial point and ending at a final point. This is accomplished through an examination and analysis of the kinematics and dynamics, followed by measurement of velocity and acceleration terms for each motor at each joint of the UR3e robot arm in a laboratory setup. Since the gained results could be implemented on any other type of trajectory, in this work as a proof of results two circular trajectories with two different radii has been investigated. By the means of these two arbitrary trajectories, the impact of change of acceleration/deceleration and velocity of each PMSM motor on each 6 joints of the robot can be examined on the overall energy losses. The results provide estimations of energy loss changes throughout the trajectory of the robot manipulator and present the results of measured reduction terms.
CRIS-Team Scopus Importer:2025-02-04
Keywords: electromechanical losses; industrial robot; motion planning; power consumption; six degree of freedom robot